Structural differences between toxic and nontoxic HypF-N oligomers. Issue 62 (18th July 2018) - Capitini, Claudia; Patel, Jayneil R.; Natalello, Antonino; D'Andrea, Cristiano; Relini, Annalisa; Jarvis, James A.; Birolo, Leila; Peduzzo, Alessia; Vendruscolo, Michele; Matteini, Paolo; Dobson, Christopher M.; De Simone, Alfonso; et al.
Abstract : We have studied two misfolded oligomeric forms of the protein HypF-N, which show similar morphologies but very different toxicities. Abstract : We have studied two misfolded oligomeric forms of the protein HypF-N, which show similar morphologies but very different toxicities. We measured over 80 intermolecular distance-dependent parameters for each oligomer type using FRET, in conjunction with solution- and solid-state NMR and other biophysical techniques. The results indicate that the formation of a highly organised hydrogen bonded core in the toxic oligomers results in the exposure of a larger number of hydrophobic residues than in the nontoxic species, causing the former to form aberrant interactions with cellular components.